Academic productivity of faculty associated with microsurgery fellowships. Issue 6 (26th December 2016) - Ruan, Qing Zhao; Ricci, Joseph A.; Silvestre, Jason; Ho, Olivia A.; Lee, Bernard T.
Abstract : Background: The Hirsch index (h‐index) is widely recognized as a reliable measure of academic productivity. While previous studies have applied the h‐index to surgical disciplines, none have analyzed microsurgery faculty. This manuscript aims to examine the h‐index of microsurgery fellowship faculty to categorize its applicability to microsurgeons as a determinant of academic output. Methods: Faculty demographics and institution characteristics were obtained from the American Society of Reconstructive Microsurgery (ASRM) and official program websites. Faculty h‐indices were calculated using the Scopus database (Elsevier, USA). Data was assessed using bivariate analysis and multiple linear regression models to determine the relationship between independent variables and total publications, career h‐index and 5‐year h‐index (h5‐index) of each faculty. Results: A total of 139 faculties from 22 programs met inclusion criteria. The median faculty age was 44 (IQR 13) and 84.9% of faculty were male. Faculty size, number of years of fellowship existence, number of fellows, FACS memberships, number of free flaps annually, and academic appointment title were significantly associated with the total publications, h‐index, and h5‐index. Multivariable analysis based on the significant independent variables demonstrated that geographical region and faculty ranks were significantly associated with the h5‐index. Conclusions: Variables associated with seniority (age, years of practice after fellowship, and academic appointment) were positively correlated with the h‐index. Given the increased use of bibliometrics in academic medicine, these results show that h‐index is a viable tool that can be used to assess research productivity among academic microsurgeons.